2018
DOI: 10.1093/ckj/sfy005
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipase 2 receptor antibody levels to predict complete spontaneous remission in primary membranous nephropathy

Abstract: BackgroundM-type phospholipase A2 receptor (APLA2R) is considered the major antigen involved in the pathogenesis of adult primary membranous nephropathy (MN), which is the leading cause of non-diabetic nephrotic syndrome. Antibodies to this antigen have been proved to be an excellent biomarker of disease activity in primary MN. In fact, preliminary data suggest that the higher the antibody level the more proteinuria, and that a decrease in antibody level precedes the remission of proteinuria, but more solid ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…Anti-PLA 2 R Ab as a Prognostic Biomarker for Primary MGN An elevated anti-PLA 2 R Ab titre is associated with poor prognosis and increased risk of progression to ESRD [9] or post kidney transplantation failure [24][25][26] whereas low anti-PLA 2 R Ab titre is associated with spontaneous remission [21,[27][28][29]. Therefore, the low prevalence of anti-PLA 2 R Ab at the end of follow-up in this study demonstrated that anti-PLA 2 R Ab is a prognostic biomarker for primary MGN as against UPCr Index level, which showed fewer subjects achieving remission at the end of follow-up.…”
Section: Prognosis Of Mgnmentioning
confidence: 99%
“…Anti-PLA 2 R Ab as a Prognostic Biomarker for Primary MGN An elevated anti-PLA 2 R Ab titre is associated with poor prognosis and increased risk of progression to ESRD [9] or post kidney transplantation failure [24][25][26] whereas low anti-PLA 2 R Ab titre is associated with spontaneous remission [21,[27][28][29]. Therefore, the low prevalence of anti-PLA 2 R Ab at the end of follow-up in this study demonstrated that anti-PLA 2 R Ab is a prognostic biomarker for primary MGN as against UPCr Index level, which showed fewer subjects achieving remission at the end of follow-up.…”
Section: Prognosis Of Mgnmentioning
confidence: 99%
“…Furthermore, in the positive group, patients with a low titer had low 24-hour proteinuria levels, high albumin levels, mild pathological damage, and higher remission rates than those with a high antibody titer, thus suggesting that the patients with low antibody titers were more likely to achieve clinical remission. Rodas et al (2019) found that spontaneous CR did not occur in patients with PLA2R levels >40 IU/mL and was less frequently observed in patients with a proteinuria level >8 g/day. Furthermore, patients with high antibody levels had a higher risk of developing ESRD.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, in the positive group, patients with a low titer had low 24-hour proteinuria levels, high albumin levels, mild pathological damage, and higher remission rates than those with a high antibody titer, thus suggesting that the patients with low antibody titers were more likely to achieve clinical remission. Lida M Rodas et al (Rodas et al 2019) found that spontaneous CR did not occur in patients with PLA2R levels >40 IU/mL and was less frequently observed in patients with a proteinuria level >8 g/day. Furthermore, patients with high antibody levels had a higher risk of developing ESRD.…”
Section: Discussionmentioning
confidence: 98%